4q-3.3=2.4q+10.78

Simple and best practice solution for 4q-3.3=2.4q+10.78 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4q-3.3=2.4q+10.78 equation:


Simplifying
4q + -3.3 = 2.4q + 10.78

Reorder the terms:
-3.3 + 4q = 2.4q + 10.78

Reorder the terms:
-3.3 + 4q = 10.78 + 2.4q

Solving
-3.3 + 4q = 10.78 + 2.4q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-2.4q' to each side of the equation.
-3.3 + 4q + -2.4q = 10.78 + 2.4q + -2.4q

Combine like terms: 4q + -2.4q = 1.6q
-3.3 + 1.6q = 10.78 + 2.4q + -2.4q

Combine like terms: 2.4q + -2.4q = 0.0
-3.3 + 1.6q = 10.78 + 0.0
-3.3 + 1.6q = 10.78

Add '3.3' to each side of the equation.
-3.3 + 3.3 + 1.6q = 10.78 + 3.3

Combine like terms: -3.3 + 3.3 = 0.0
0.0 + 1.6q = 10.78 + 3.3
1.6q = 10.78 + 3.3

Combine like terms: 10.78 + 3.3 = 14.08
1.6q = 14.08

Divide each side by '1.6'.
q = 8.8

Simplifying
q = 8.8

See similar equations:

| 7(2x+3)+8=-6(7x+4)+3x | | -2x+6x-3= | | (-4t+8)(4t+1)=0 | | -5X+6/5=9X+7/2 | | 3x-5y=19 | | 180-x=2x+12 | | 3(2x+3)=-2x+2 | | 7(x-12)-11=22x-275 | | 5(2x-5)-3(x+1)-18x= | | (n-4)(n+4)=n-4 | | 2x-5=55+7x | | -(3)/(y-5)=(-(8)/5y-25)+1 | | -6(x+4)+158=13+25 | | t(3t+27)=66 | | -4/6x=12/24 | | 4x+56=5432 | | 5+7x=-x+53 | | -(2x^2y+4z)+4z-7x^2y= | | 8-2w=2 | | -2/6x=6/12 | | 84=12(12y+3) | | 2x+3*x-1= | | 7x-43=52 | | 3X+3/5=-2X-7/4 | | 4x^2-20x+10=0 | | -14-(-12)=x/2 | | 7-3(5t-10)=-67 | | x+3=12-1x | | 49=3x+9 | | -5x-10=2x+11 | | 52=3x+7 | | 17x+30=4(3x+6)+5x+6 |

Equations solver categories